Zależność kondycji ekonomiczno-finansowej przedsiębiorstw oraz sytuacji lokalnych rynków pracy - Wójciak, Mirosław (The dependence of economical and financial condition and local labour markets, 2006)
In the paper the dependence of economical and financial condition and local labour markets was presented. To reach this target the hierarchical aglomerative methods were used that enabled to group the districts in homogenous sets and linear ordering to find out the conditio level of companies and the situation of local labour markets. Basic financial and economical ratios were used as diagnostic characteristics. The next step of analysis was to confront the results obtained with basic characteristics of labour market describing the current rate of unemployment as well as its flexibility in particular districts.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 445-455